Comparison of accuracy between dental and skeletal age in the estimation of chronological age of Down syndrome individuals - Hala, Leila Abou [UNESP]; Moraes, Mari Eli Leonelli de [UNESP]; Villaça-Carvalho, Maria Fernanda Lima [UNESP]; de Castro Lopes, Sérgio Lúcio Pereira; Gamba, Thiago de Oliveira (Elsevier, 2016)
This study aimed to evaluate the accuracy of dental age (DA) and skeletal age (SA) methods in order to estimate chronological age (CA) in individuals with Down syndrome (DS), contributing to the Forensic Dentistry and making the identification of these individuals age possible. For this, 278 images of individuals were selected and divided in 2 groups: 216 non-DS patients and 62 with DS. At first, DA was evaluated by Nolla method, on panoramic radiographs, followed by SA, evaluated by Greulich and Pyle method. The linear correlation coefficient of Pearson was used for the analysis of concordance between the methods. Paired t-test with confidence interval was used to evaluate the accuracy and Bland and Altman method was applied to estimate limits of concordance. Complementary to this first analysis, descriptive statistics and ANOVA test were applied for comparison among chronological age (CA), dental age (DA) and skeletal age (SA), with a significance level of 95% (p ≥ 0.05), ordering to observe the differences among them. DA, estimated by Nolla, is underestimated in both, DS and non-DS individuals, and it is more notable in DS individuals. SA estimated by Greulich and Pyle method is overestimated, except for non-DS males. The range of variance is greater in SA and DS than DA and non-DS individuals, respectively. A greater accordance was found for DA × CA if compared to SA × CA, indicating that DA, estimated by Nolla method, is more accurate than SA, evaluated by Greulich and Pyle method, for estimating CA of both, DS and non-DS individuals. However, neither method seems to be precise and more caution is required for age estimation in DS individuals.
Keywords: Age determination by teeth; Bone development; Down syndrome; Forensic anthropology population data; Tooth mineralization